ANALISIS PENGARUH HARGA, KUALITAS PRODUK DAN POSITIVE WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI PADA PENGGUNA IPHONE DI FAKULTAS KEDOKTERAN UNIVERSITAS DIPONEGORO) - Giovani Erlitna, Kesia; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2018)
Communication tool is one of the needs that is not less important in human life. One type of communication tool that is often used at this time is a smartphone. In this study, the author saw a decline in sales of iPhone products from the results of Top Brand Index survey. In addition, there are differences in the results of previous research and research gap. The purpose of this research is to analyze the influence of price, product quality and positive word of mouth against purchasing decision with the brand image as an intervening variable. The research was conducted for students of Faculty of Medicine at Diponegoro University. The samples in this research as much as 100 respondents. With the method of collecting data through questionnaries and sampling method in this research is non probability sampling with purposive sampling technique. This research uses the Partial Least Square analysis techniques, which are being estimated by the program SmartPLS 3.2.7. The results of this study shows that price has positive and significant effect on brand image, product quality has positive and significant effect on brand image, positive word of mouth has positive and significant effect on brand image. It is also known that brand image is proven to mediate price, product quality and positive word of mouth on purchasing decision.